Believing and Seeing. (December 2017) - Prosperi, Paolo
This article reconsiders the relationship between vision and faith, recuperating an understanding of the "ray of darkness" accented by Church Fathers such as Gregory of Nyssa and Dionysius for a fuller understanding of the beatific vision. Vision and faith are not ultimately two opposite movements, but rather two inseparable aspects of one dynamism leading to a knowing union with God that is "ever-more."